Aransemen Lagu Amazing Grace Karya John Newton Dengan Quartet Saxophone Di Prodi Pendidikan Musik Gereja IAKN Tarutung - Rico Andrian Saragih; Aprilnaldi Patiaraja Simorangkir; Robert K.A Simangunsong; Diana Martini Situmeang; Rowilson Nadeak (LPPM Politeknik Pratama, 2024)
This research aims to arrange the song Amazing Grace for the Saxophone Quartet playing with the development of modern music science which is still hot to be studied. This thesis uses qualitative research methods. This research was carried out by collecting information through field research to be processed into accurate data. The processes carried out for data collection are: interviews and documentation. First, this thesis explains how to arrange the song Amazing Grace with Quartet Saxophone, then understand the melody of the song Amazing Grace to adapt it to the variations in rhythm and harmony of modern music in balance with the Quartet Saxophone instrument. So this research resulted in an arrangement of the song Amazing Grace with a Saxophone Quartet with a modern musical feel using extended harmonies with balanced inversions, rhythm adjustments with more varied construts and the selection of balanced melodic contours. This research provides information for Arrangers to understand the broad knowledge of music in order to produce Church Music Arrangements with a balanced, Modern feel. To understand how to arrange songs with a modern feel requires broad insight and consistent practice. Apart from that, this thesis concludes that the development of modern music science is not only to improve the results of commercial musical arrangements, but for the glory of God with balanced musical arrangements.